1966
DOI: 10.2172/4706619
|View full text |Cite
|
Sign up to set email alerts
|

HIGH PERFORMANCE UO$sub 2$ PROGRAM. DIMENSIONAL CHANGES IN HIGH PERFORMANCE POWDER AND PELLET FUEL RODS: PROFILOMETER STUDIES.

Abstract: This report is the eighth in a series summarizing the results obtained during the High Performance uo 2 Program sponsored by the joint U.S.-EURATOM Research and Development Program. The entire report series constitutes the final summary report of the program and will be issued under the single report number GEAP-5100. Major technical topics in the final report will be designated by the sequence GEAP-5100-1 through 5100-11. The appendices, describing the individual pressurized water loop fuel assemblies irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1977
1977

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lustman pointed out that in the presence of such a (24) thermal gradient, a fuel pellet deforms to the hourglass shape which may produce strain concentrations in the cladding and result in circumferential ridging of the cladding. According to Hoffman et al, ridges are of particular concern because (60) they make that part of the cladding most susceptible to failure (The three types of strain (30) concentration are: axial strain concentration, hoop strain from longitudinal cracks in the fuel surface, and hoop strain from ridging.) So far it appears that no one has made any study Of the effects of "prestrain" in Zirca Zoy on #ze strain to fa€Zure in either the irradiated or non€pradiated condition.…”
Section: Fuel Pellet Thermal Distortion ("Hourglassing")mentioning
confidence: 99%
See 1 more Smart Citation
“…Lustman pointed out that in the presence of such a (24) thermal gradient, a fuel pellet deforms to the hourglass shape which may produce strain concentrations in the cladding and result in circumferential ridging of the cladding. According to Hoffman et al, ridges are of particular concern because (60) they make that part of the cladding most susceptible to failure (The three types of strain (30) concentration are: axial strain concentration, hoop strain from longitudinal cracks in the fuel surface, and hoop strain from ridging.) So far it appears that no one has made any study Of the effects of "prestrain" in Zirca Zoy on #ze strain to fa€Zure in either the irradiated or non€pradiated condition.…”
Section: Fuel Pellet Thermal Distortion ("Hourglassing")mentioning
confidence: 99%
“…Hoffman et al studied annular pellet behavior (60) and indicated that the annular configuration appeared to affect the shape distortion (hourglassing) of the cylindrical body in a manner that was different than that for solid pellets. reported that after volatile impuri- (34) ties are released inside the fuel rod, the disposition of those gaseous impurities is not well understood.…”
Section: (5)mentioning
confidence: 99%